Assessment of potential climate change impacts on montane forests in the Peruvian Andes: Implications for conservation prioritization - Bax, Vincent; Castro-Nuñez, Augusto Carlos; Francesconi, Wendy (MDPI, 2021)
This study examines climate change impacts in the Peruvian Andes, with a specific focus on tropical montane forest ecosystems, which are particularly susceptible to climate change. Using an ensemble of classification models coupled with different climate change scenarios, we estimate high and low potential impacts on montane forest, by projecting which areas will become climatically unsuitable to support montane forest ecosystems by 2070. These projections are subsequently used to examine potential impacts on protected areas containing montane forest.